Development Of Stem-Based Interactive Multimedia On Human Digestive System For Elementary School - Liza Ayu Khairani; Ely Djulia; Wawan Bunawan (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2023)
This study aims to determine the feasibility of using STEM-based interactive multimedia on human digestive system for elementary school. This research is a Research and Development which refers to the ADDIE model which consists of 5 stages, namely the analysis, design, development, implementation, and evaluation stages. Data collection techniques in this study were observation, interviews, and validation. This research was conducted in class V. The results showed the multimedia was valid in terms of media by 91,20%, in terms of material by 94.44%, and interms of instructional design by 93,33%. This multimedia is â€œVery Feasibleâ€ for participants touse in learning education.Â Furthermore, the results of the assessment from the teacher obtained 93% and limited trials by students obtainedÂ 94%Â whichÂ isÂ inÂ theÂ veryÂ goodÂ category.Keywords:Â Interactive Multimedia, STEM, Elementary School.